Fibrous all-in-one monolith electrodes with a biological gluing layer and a membrane shell for weavable lithium-ion batteries - Ha, Sung Hoon; Kim, Soo Jin; Kim, Hyoungjun; Lee, Chae Won; Shin, Kyu Hang; Park, Hae Won; Kim, Soonwoo; Lim, Yein; Yi, Hyunjung; Lim, Jung Ah; Lee, Yun Jung (ROYAL SOC CHEMISTRY, 2018)
The increasing demand for wearable devices ultimately requires the development of energy storage devices with wide structural versatility, lightweight and high energy density. Although various flexible batteries have been developed based on two-dimensional and one-dimensional platforms, truly weavable batteries with high capacity and elongation capability have not been materialized yet. Herein, we report weavable lithium ion batteries (LIBs) with high capacity by developing fibrous all-in-one electrode threads based on nanosized hybrid active layers with a biological gluing inner layer and a membrane shell. The thread consists of four distinct concentric structures, a carbon fiber core as a current collector, a conductive biological gluing layer, nanohybrid active materials, and a porous membrane layer. Nanosized LiFePO4/C-rGO and Li4Ti5O12/rGO are used for cathode and anode threads, respectively. This unique all-in-one structure combined with an inline coating approach ensures flexibility and mechanical stability with a high linear capacity of 1.6 mA h cm(-1). These features all together allow for various assembly schemes such as twisting and hierarchical weaving, enabling fabric LIBs to show 50% elongation via encoded structural deformation.
Keywords: WEARABLE ENERGY-STORAGE; CONDUCTIVE NANOMESH; FIBER; PERFORMANCE; YARNS; PAPER; OXIDE; SUPERCAPACITORS; PROGRESS; CATHODE